2009
DOI: 10.1093/ntr/ntp133
|View full text |Cite
|
Sign up to set email alerts
|

The behavioral ecology of secondhand smoke exposure: A pathway to complete tobacco control

Abstract: of the behavior of many people on multiple levels, and a broad systems approach to understanding both the individual ' s and the population ' s behavior is critical to achieving health promotion for all. Investigators cannot ignore the behavior of politicians who enact legislative policies that infl uence public health research, the behavior of medical care providers and insurers, and the behavior of industries (e.g., pharmaceuticals, tobacco) that may profi t from behavior that prevents disease or that harms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
111
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 69 publications
0
111
0
Order By: Relevance
“…Logistic regression models regressed smoking ban on each of the demographic and theoretical mediator variables described above to examine the association between the DV bans and mediator variables. Finally, the relative contribution of theoretical mediators to the likelihood of having a smoking ban in the home was estimated by random intercept regression models in order to adjust for cluster sampling and to improve fit due to variation in intercepts among sample clusters (Hovell & Hughes, 2009;Rabe-Hesketh & Skrondal, 2008). Models were examined to test whether theoretical mediators remained associated with the DV, after controlling for city and demographics, and to determine if reduction in the direct effect between the independent variable and the DV was observed when controlling for mediation variables, consistent with evidence of mediation (Baron & Kenny, 1986;Kraemer, Kiernan, Essex, & Kupfer, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Logistic regression models regressed smoking ban on each of the demographic and theoretical mediator variables described above to examine the association between the DV bans and mediator variables. Finally, the relative contribution of theoretical mediators to the likelihood of having a smoking ban in the home was estimated by random intercept regression models in order to adjust for cluster sampling and to improve fit due to variation in intercepts among sample clusters (Hovell & Hughes, 2009;Rabe-Hesketh & Skrondal, 2008). Models were examined to test whether theoretical mediators remained associated with the DV, after controlling for city and demographics, and to determine if reduction in the direct effect between the independent variable and the DV was observed when controlling for mediation variables, consistent with evidence of mediation (Baron & Kenny, 1986;Kraemer, Kiernan, Essex, & Kupfer, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This model suggests that when antitobacco sentiments become normative, they are likely to support government regulations that restrict the sale and use of tobacco, leading to synergistic antitobacco policies that reflect contingencies (e.g., taxation, fines) that define a more complete and powerful antitobacco culture (Glantz, 1993). Hovell and Hughes (2009) have suggested that engineering changes in culture that result in fewer and fewer microenvironments in which smokers can smoke, may be the most powerful means of preventing smoking population wide.…”
Section: Discussionmentioning
confidence: 99%
“…Because our proactive recruitment components emphasized a research staff-WIC staff partnership that coordinated clinic-specific recruitment activities and incentivized WIC staff's recruitment efforts, we suggest that associative learning theories and the Behavioral Ecological Model (BEM) [38][39][40] provide a suitable framework for interpreting the results of this study. Associative learning theories assert that patient retention can be facilitated by implementing reinforcing consequences for ongoing participation that are delivered at individual, family, or clinic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hovell and Hughes (2009) have taken these frames to their next logical extension with application to SHSe where more specific and testable deductions may be made. Herein, we extended these deductions by applying the logic of distal and proximal mediation and moderation to Koreans and Korean Americans, and their home smoking restrictions.…”
Section: Discussionmentioning
confidence: 99%